Investigating the Level of Mathematics Anxiety among Junior High School Pupils - Koomson, David; Ohene Boateng, Francis; Kwesi Lotey, Ebenezer (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
Mathematics is a fascinating and perplexing subject that is constantly evolving in a variety of scientific fields. Naturally, it is amazing and beautiful to use mathematics to solve a real-life problem and comprehend it. However, most people fear mathematics. The goal of this research was to explore Ghanaian Junior High School pupils' level of anxiety in mathematics at two different schools.. A Likert-Scale type of questionnaire on mathematics anxiety was given to 120 pupils who were randomly selected from the population to answer voluntarily. Descriptive and inferential analysis were both used to analysis the responses from the pupils. It was revealed that mathematics anxiety was reported to be high among junior high school pupils. It was also found that female pupils had greater levels of mathematics anxiety than male pupils. Practical recommendations are provided based on the findings of the study.